Hard and Soft Tissue Augmentation with Single-Implant Restoration in the Esthetic Zone - Igor Ashurko; Nataliia Blagushina; Anisa Borodiy; Mary Magdalyanova (Case Reports in Dentistry)
The removal of the central incisor of the upper jaw is a challenging process, since the restoration of a single implant in the esthetic zone is of great responsibility. When tooth extraction with immediate implant placement is not possible, modern protocols imply the use of the socket preservation technique. This method of preserving socket properties significantly reduces changes that occur during the healing process of the postextracted area and along with soft tissue augmentation allows to achieve a satisfying aesthetic result. The aim of present case report is to assess capabilities of socket preservation concept and application of soft tissue augmentation in the anterior maxillary region. The treatment steps of a 35-year-old woman who needed to remove tooth 11 with further dental implant placement are described. The clinical case is of interest because after socket preservation and soft tissue augmentation, an acceptable aesthetic result was not reached. However, additional soft tissue augmentation made it possible to achieve the desired result, which was stable for 7 years.